Assessment of post-partum physical exercise practice and its associated factors among women in postpartum period, in West Wollega zone, Oromia, Ethiopia - Yadeta, Tegegne; Belema, Daniel; Ahmad, Seifedin; Sirage, Nurye; Ali, Abubeker Seid; Ali, Kedir; Yimer, Ali (Frontiers in Public Health, 2025)
BackgroundThe postnatal period, spanning the initial 6 weeks after childbirth, brings about a range of difficulties for mothers globally, encompassing psychological, physiological, and biological shifts. Incorporating regular physical activity during this phase has demonstrated the potential to mitigate the chances of chronic metabolic disorders. Nevertheless, there is a lack of comprehensive understanding regarding women’s engagement in postpartum physical exercise during this time.MethodsThe research employed a community-based cross-sectional study design carried out between April 20 and May 20, 2023. A sample of 422 women was chosen through a simple random sampling method utilizing computer-generated random numbers. The data was inputted into Epi-Data 4.6 and processed with SPSS 26. Descriptive statistics and logistic regression were employed for the analysis. Variables with a p-value below 0.25 in the bi-variable analysis were included in the multivariable analysis, and those with a p-value under 0.05 in the multivariable analysis were considered as significantly associated factors. The results were presented using graphs and tables.ResultThis research involved 416 women, achieving a response rate of 98.6%. The prevalence of postpartum physical exercise practice among the participants was determined to be 19.5% (95% CI: 12.03–22.50). Several factors were independently associated with postpartum physical exercise practice: Women with a college education or higher had nearly three times greater odds of engaging in postpartum physical exercise (AOR = 2.97, 95% CI: 1.14, 7.80). Being employed in a government institution was associated with a 2.14 times higher likelihood of participating in postpartum physical exercise (AOR = 2.14; 95% CI: 1.96, 4.74). Primipara women had 2.8 times higher odds of practicing postpartum physical exercise (AOR = 2.80, 95% CI: 1.72, 4.59). Women who had exercised before pregnancy were more likely to continue postpartum physical exercise, with 5.1 times higher odds (AOR = 5.10; 95% CI: 2.78, 9.29). Possessing good knowledge about postpartum physical exercise was associated with 2.3 times greater odds of engaging in such exercise (AOR = 2.30; 95% CI: 1.20, 4.40).ConclusionThe study indicates that the majority of participants were not participating in postpartum physical exercise. Nevertheless, women with higher levels of education, government jobs, primipara mothers, prior exercise experience before pregnancy, and a good knowledge of postpartum physical exercise were more inclined to engage in it. These results underscore the need to increase awareness among healthcare providers and other relevant organizations about the advantages of postpartum physical exercise in preventing complications during the postpartum phase.